2010
DOI: 10.1002/ijc.25404
|View full text |Cite
|
Sign up to set email alerts
|

TIMP‐3 promotes apoptosis in nonadherent small cell lung carcinoma cells lacking functional death receptor pathway

Abstract: Tissue inhibitor of metalloproteinases-3 (TIMP-3) has previously been identified as a tumor suppressor for adherent malignant and normal cells. TIMP-3 inhibits adhesion of cells to extracellular matrix and promotes apoptosis through death receptoractivated, caspase-8-mediated pathway. Here, we have studied the effect of adenovirally mediated overexpression of TIMP-3 on small cell lung cancer (SCLC) cell lines SW2 and N417, which grow in suspension and lack functional caspase-8. The results show that adenoviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…19 TIMP3 induces apoptosis through both the caspase-dependent and caspase-independent pathways. 20 In our study, Ad-TIMP3 induced apoptotic morphology in cancer cells. Overexpression of TIMP3 induces release of cytochrome-c and activates the caspase-8 and caspase-9 pathways, both resulting in cancer cell apoptosis.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…19 TIMP3 induces apoptosis through both the caspase-dependent and caspase-independent pathways. 20 In our study, Ad-TIMP3 induced apoptotic morphology in cancer cells. Overexpression of TIMP3 induces release of cytochrome-c and activates the caspase-8 and caspase-9 pathways, both resulting in cancer cell apoptosis.…”
Section: Discussionsupporting
confidence: 50%
“…21 Bond et al 21 reported that TIMP3 induces apoptosis through a Fas-associated death domain-dependent type II apoptotic pathway. On the other hand, Kallio et al 20 showed that TIMP3 is capable of inducing apoptosis in the absence of caspase-8 activation in human small cell lung carcinoma cells, suggesting other pathways besides death receptor signaling. Our previous study also showed that Ad-TIMP3 induced p53 expression in human cancer cell lines Hela and Caski.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other TIMP variants (TIMP-1, 2, and 4), TIMP-3 has poor aqueous solubility and is a component of the ECM (5). Studies have demonstrated that TIMP-3 might function as a potential tumor suppressor gene through induction of tumor cell apoptosis, prevention of tumor ECM remodeling, and inhibition of tumor-derived angiogenic activity (5,6) The expression of TIMP-3 is silenced in various types of malignant carcinoma (7). Regulation of TIMP-3 expression may be influenced by many upstream and downstream transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence is found by the observation that a number of genes of the identified ''Toxicological Classes'' is commonly modulated in both hSKP-HPC and hHEP exposed to APAP. The upregulated genes, BCL2L11, FOS, HMOX1, TIMP3 and AHR are all associated either to cytotoxic responses or induction of apoptosis [72][73][74][75][76][77] and might be useful molecular biomarkers for hepatotoxicity.…”
mentioning
confidence: 99%